The Face as Image: Witnessing, Minimizing Harm and Testimony - Kerstin Roger; Andrew Hatala (International Journal of Qualitative Methods)
This paper explores the human face as an important image, and as visual data, in the context of academic work. We explore its philosophical value through a discussion of testimony and witnessing, visual data through the interface between academia and social media in the broader world, and with a reflection of university-based ethics. We explore the example of academic publication of a participant’s face as presented in peer reviewed journals, online and open access, or through other academic deliverables and printed content. The question of how we as researchers and members of REBs (Research Ethic Boards) should act as protectors of participants who want to reveal their faces as image data in research is an interesting one. The paper explores the context of ‘image testimony’, in light of literature on witnessing and trends in social media. The face as an image online has become an important “voice”. The face as visual image then also emerges as relevant in ethics, through data collection, and the ongoing work of researchers. In the context of modern digital media communications, it is hard to imagine the success of social media platforms without human faces, personal choices made by individuals posting selfies while eating, demonstrating, or going on nature hikes. In the broadening cultural narrative of the face as digital image, we reflect on where the university and the REB stand. Our discussion explores ethical considerations and makes recommendations.